Evaluation of apical extrusion of debris and centering ability in different nickel-titanium files during curved root canal preparation - Dongsheng Yu; Li Guo; Jing Gao; Jie Liu; Deqin Yang (BMC, 2023)
Abstract Background Curved root canals lead to difficulties in cleaning, shaping and filling the root canal system. Apical extrusion of debris and root canal transportation are important factors causing postoperative complications. In clinical practice, commonly selected instruments include multifile NiTi systems, such as M3-Pro PLUS (M3-PRO), Orodeka Plex 2.0 (ODP), Rotate (ROT), and Protaper Gold (PTG), as well as single-file NiTi systems, such as M3-L Platinum 2019 (M3L), Waveone Gold (WOG), and Reciproc Blue (RCB). This study aimed to comprehensively evaluate the differences in the apical extrusion of debris and centering ability of the above NiTi files. Methods Seventy 3D-printed resin teeth were used (n = 10). The apically extruded debris was collected in a preweighed centrifuge tube. The resin teeth with or without root canal preparation were cut into separate cross sections at 1 mm, 3 mm, 5 mm, and 7 mm away from the root apex, and then the root canal transportation and centering ratio of each cross section were calculated. Results Apical extrusion of debris was highest in RCB but lowest in OD-P (P < 0.05). Root call deviation was lowest in ROT at the 3 mm level, in PTG at the 5 mm level, and in PTG and ROT at the 7 mm level (P < 0.05). The centering ratio of NiTi files was highest in the RCB group at the 3 mm level, in the PTG group at the 5 mm level, in the ROT group at the 7 mm level (P < 0.05). Conclusions For NiTi files with the same system, the cross-sectional design is the greatest factor affecting the extrusion of debris, and motion mode is the second. In addition, the multifile system could reduce the degree of root canal transportation.